Relatório de Pesquisa NESCoM 2021 - Costalonga, Leandro; Neves, Marcus Vinícius das (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19465, 2021)
The NESCoM is a multidisciplinary research centre formed by musicians, engineers and computer scientists. This paper reports the ongoing projects and developments over the last two years, thus it is an update over the research report published in 2019. As a Brazilian research group, with solid international collaboration, we have opted to intercalate the language used to write the report, therefore the 2021 version is written in Portuguese. The main projects developed in these two years timeframe are related to interaction design based on (bio)musicality, robotic music performance, and ubiquitous music. In addition, a strong artistic production is also described. If you are interested to get to know more about the projects, do not hesitate to contact us.